Does culture condition of reduced oxygen pressure helps in embryo quality? A prospective randomized study - Patil, Deepak (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Embryo quality is of paramount importance in an in vitro fertilization and embryo transfer (IVF-ET) cycle. A healthy embryo leads to a robust pregnancy. Incubation in an ideal atmosphere is essential requirement in an IVF-ET cycle. Methods: Traditionally carbon dioxide incubator with sensors for carbon dioxide levels and temperature has been used widely. We compared the quality of these embryos to incubation in hypoxic condition by addition of nitrogen. Oxygen levels were brought to 5% as compared to 21% in room air. Results: Ladies with high body mass index (BMI) and advanced age had more embryos available for transfer. More embryos reached day 3 and day 5, thus increasing availability for cryopreservation. The fragmentation rate and fertilization failure were less. Pregnancy rate was definitely improved as compared to traditional incubation. Conclusions: Hypoxic incubation condition leads to better embryo health. This translates into improved and efficient cycle outcome.